2018
DOI: 10.5114/pg.2018.74557
|View full text |Cite
|
Sign up to set email alerts
|

Early biliary drainage is associated with favourable outcomes in critically-ill patients with acute cholangitis

Abstract: IntroductionAcute cholangitis (AC) is a clinical condition that requires prompt medical management with IV fluids, antibiotics, and biliary drainage (BD). The optimal timing for BD remains unclear.AimTo investigate the effect of biliary drainage timing on clinical outcomes in AC.Material and methodsWe conducted a retrospective study of patients with AC admitted to the ICU using the Multiparameter Intelligent Monitoring in Intensive Care III (MIMIC-III) database. Emergency department to BD time, hospital death,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 17 publications
0
23
1
Order By: Relevance
“…But it has decreased to 10-30% since 1980, with the development of endoscopic biliary drainage techniques and the various associated therapeutic modalities [ 1 , 7 , 8 ]. Current mortality rates vary between 9.6% and 37% [ 6 , 9 11 ], and death is most often due to a multiorgan failure related to a refractory septic shock [ 1 ]. This is consistent with our results which showed a mortality rate of 28% and refractory septic shock as the leading cause of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it has decreased to 10-30% since 1980, with the development of endoscopic biliary drainage techniques and the various associated therapeutic modalities [ 1 , 7 , 8 ]. Current mortality rates vary between 9.6% and 37% [ 6 , 9 11 ], and death is most often due to a multiorgan failure related to a refractory septic shock [ 1 ]. This is consistent with our results which showed a mortality rate of 28% and refractory septic shock as the leading cause of death.…”
Section: Discussionmentioning
confidence: 99%
“…Procalcitonin has been proposed by some authors as a predictive indicator of severity and therefore of urgent biliary decompression [ 20 ], but this needs to be validated by more well-designed studies. According to previous studies, biliary drainage is the most important factors associated with mortality [ 9 11 ]. Time to biliary decompression did not stand out as a prognosis factor in our series.…”
Section: Discussionmentioning
confidence: 99%
“…A recent single center study from Denmark found that ERCP within 24 h was associated with lower 30-d mortality (OR 0.23, 95%CI: 0.05-0.95)[4]. Several similar retrospective studies did not find a difference in mortality between early and late ERCP[6-9]. This could be related to the low statistical power of some of these studies, and the low incidence of mortality in some cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Several small, single center retrospective studies found that early ERCP (within 24 to 72 h of admission) is associated with lower in hospital and 30-d mortality, compared to late ERCP[2-5]. Other studies did not show a difference in mortality between early and late ERCP[6-9]. The association of early ERCP with outcomes could vary in patients depending on their disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ERCP was efficient, considered as optimal in 70% of the case. Non-optimal procedure may be due to infiltrating tumor-related AC supporting that a non-gallstone biliary obstacle is an independent pejorative prognosis factor [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%